La Représentation du Discours Autre - Authier-Revuz, Jacqueline (Études de linguistique française, 2020)
This book offers a general model of reported speech that relies on clear, well-argued theoretical choices in order to describe accurately the diversity of observed situations. The metalanguage/alterity articulation is critically discussed at various levels (language, discourse, subject) where a central function of differential auto-configuration takes place.